Application of statistical process control in healthcare improvement: systematic review. Issue 5 (3rd October 2007) - Thor, Johan; Lundberg, Jonas; Ask, Jakob; Olsson, Jesper; Carli, Cheryl; Härenstam, Karin Pukk; Brommels, Mats
Abstract : Objective: To systematically review the literature regarding how statistical process control—with control charts as a core tool—has been applied to healthcare quality improvement, and to examine the benefits, limitations, barriers and facilitating factors related to such application. Data sources: Original articles found in relevant databases, including Web of Science and Medline, covering the period 1966 to June 2004. Study selection: From 311 articles, 57 empirical studies, published between 1990 and 2004, met the inclusion criteria. Methods: A standardised data abstraction form was used for extracting data relevant to the review questions, and the data were analysed thematically. Results: Statistical process control was applied in a wide range of settings and specialties, at diverse levels of organisation and directly by patients, using 97 different variables. The review revealed 12 categories of benefits, 6 categories of limitations, 10 categories of barriers, and 23 factors that facilitate its application and all are fully referenced in this report. Statistical process control helped different actors manage change and improve healthcare processes. It also enabled patients with, for example asthma or diabetes mellitus, to manage their own health, and thus has therapeutic qualities. Its power hinges on correct and smart application, which is not necessarily a trivial task. This review catalogues 11 approaches to such smart application, including risk adjustment and data stratification. Conclusion: Statistical process control is a versatile tool which can help diverse stakeholders to manage change in healthcare and improve patients' health.